Neonatal Herpes Simplex Encephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The sequential EEGs of 15 neonates with herpes simplex virus meningoencephalitis were correlated with clinical and laboratory findings at the Children's Hospital, Harvard Medical School, and Massachusetts General Hospital, Boston, MA.